Financialisation', distribution, capital accumulation and productivity growth in a Post-Kaleckian model - Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2009)
Focussing on the long-run effects of 'financialisation' and increasing shareholder power in a simple Post-Kaleckian endogenous growth model, we examine the effects of increasing shareholder power on the demand regime, on the productivity regime, and on the overall regime of the model. Under special conditions increasing shareholder power may have positive effects on capital accumulation and productivity growth and hence on potential growth of the economy. However, such a regime does not only require directly positive - or under certain conditions only weakly negative - effects of increasing shareholder power on the productivity regime. It also requires expansive - or under special circumstances only weakly contractive - effects of increasing shareholder power on capital accumulation via the demand regime of the economy. Both conditions have recently been questioned on empirical grounds, so that an overall long-run 'contractive' regime seems to be the most likely outcome of 'financialisation' rising shareholder power and pronounced shareholder value orientation.
Keywords: E12; E21; E22; E25; O16; O41; 330; Financialisation; distribution; capital accumulation; productivity growth; Kaleckian model